Effect of acid hydrolysis on the structural and antioxidant characteristics of β-glucan extracted from Qingke (Tibetan hulless barley) - Zhao, Lan; Lin, Shuwei; Lin, Jingying; Wu, Jia; Chen, Huibin (Frontiers in Nutrition, 2022)
In this study, we explored the effect of acid hydrolysis on the molecular, structural, rheological, thermal, and antioxidant characteristics of Qingke β-glucan. The molecular weights of the Qingke β-glucan ranged from 155 to 510 kDa. The results of the structural analysis by NMR spectroscopy, X-ray diffraction, and FTIR spectroscopy indicated that acid hydrolysis did not change the primary functional groups of β-glucans. The rheological behavior of β-glucan without and with acid hydrolysis can be described as pseudoplastic and Newtonian, respectively. The DSC curves of the β-glucans with high molecular weights showed the highest transition temperature. The 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging activity and the reducing power of soluble β-glucans in Qingke showed a dose-dependent pattern. Meanwhile, the antioxidant activities of Qingke β-glucan of different molecular weights were similar. This study demostrated that the acid hydrolysis almost have no effect on antioxidant activity of Qingke β-glucans.